Factors affecting the properties of PLA/CaSO4 composites: homogeneity and interactions (eXPRESS Polymer Letters)
Composites were prepared from poly(lactic acid) (PLA) and a natural CaSO4 filler to study the developed structure and the interaction of the components. The filler was characterized very thoroughly by several techniques and the results indicated that the filler contains a considerable amount of small particles with size much below the volume average size of 4.4 µm. The presence of these small particles did not result in inhomogeneity, considerable extent of aggregation was not observed in the composites. The filler was coated with stearic acid to modify interactions and optimum coverage corresponded to the amount estimated from the specific surface area of the filler. Mechanical properties changed only slightly with increasing amounts of the uncoated filler, but coating resulted in a drastic change of tensile properties and deformation behavior. Considerable plastic flow was observed around filler particles on the fracture surface of broken specimens. The quantitative estimation of interfacial interactions and their comparison to existing data proved that the interaction of PLA and CaSO4 corresponds to values observed in other mineral filled polymers. On the other hand, the reinforcing effect of the coated filler is extremely poor indicating almost zero interaction. Additional experiments proved that considerable amount of stearic acid dissolves in PLA and plasticizes the polymer. Stearic acid seems to desorb also from the surface of the filler, dissolve in the polymer and modify matrix properties.